The privacy fix : how to preserve privacy in the onslaught of surveillance - Sloan, Robert H.; Warner, Richard, 1946- (Cambridge : Cambridge University Press, 2021)
Online surveillance of our behavior by private companies is on the increase, particularly through the Internet of Things and the increasing use of algorithmic decision-making. This troubling trend undermines privacy and increasingly threatens our ability to control how information about us is shared and used. Written by a computer scientist and a legal scholar, The Privacy Fix proposes a set of evidence-based, practical solutions that will help solve this problem. Requiring no technical or legal expertise, the book explains complicated concepts in clear, straightforward language. Bridging the gap between computer scientists, economists, lawyers, and public policy makers, this book provides theoretically and practically sound public policy guidance about how to preserve privacy in the onslaught of surveillance. It emphasizes the need to make tradeoffs among the complex concerns that arise, and it outlines a practical norm-creation process to do so.
Surveillance and self-realization -- Artificial intelligence enhanced surveillance -- Social roles, common knowledge, and coordination -- Coordination norms -- Notice and choice : the allure and the illusion -- The threat of collapse, the prospects of resistance -- Acquiescence -- Accept or take control? -- Regulating artificial intlligence.
Title from publisher's bibliographic system (viewed on 11 Oct 2021).
Keywords: Privacy, Right of; Self-realization.; Electronic surveillance -- Government policy; Artificial intelligence -- Law and legislation; Electronic monitoring in the workplace -- Law and legislation; Electronic surveillance -- Law and legislation